2004
DOI: 10.1093/ei/cbh061
|View full text |Cite
|
Sign up to set email alerts
|

Trade and Wage Inequality in Developing Countries

Abstract: In this article we provide a theoretical analysis of the possible impact of trade and fragmentation on the skilled–unskilled wage gap in a small developing economy. In particular, we illustrate the possibility of a decline in the relative wage of the unskilled labor following an improvement in the terms of trade. (JEL F1, F11, F12)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
52
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(53 citation statements)
references
References 10 publications
1
52
0
Order By: Relevance
“…It is quite perplexing as to why the relative wage inequality has deteriorated, especially when as per the baseline 2×2×2 Heckscher-OhlinSamuelson trade model, economic liberalization was expected to improve the wage inequality in the developing economies following increases in the prices of the export commodities as these are generally exporters of commodities that are intensive in the use of unskilled labour. The scanty theoretical literature explaining the deteriorating wage inequality in the developing countries includes works of Feenstra and Hanson (1996), Yabuuchi and Chaudhuri (2007) and Marjit, Beladi and Chakrabarti (2004). They have shown how trade liberalization, international migration of labour and inflows of foreign capital might produce unfavourable effects on the wage inequality in the South given the specific structural characteristics of the less developed countries, such as features of labour markets, structures of production, nature of capital mobility etc.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is quite perplexing as to why the relative wage inequality has deteriorated, especially when as per the baseline 2×2×2 Heckscher-OhlinSamuelson trade model, economic liberalization was expected to improve the wage inequality in the developing economies following increases in the prices of the export commodities as these are generally exporters of commodities that are intensive in the use of unskilled labour. The scanty theoretical literature explaining the deteriorating wage inequality in the developing countries includes works of Feenstra and Hanson (1996), Yabuuchi and Chaudhuri (2007) and Marjit, Beladi and Chakrabarti (2004). They have shown how trade liberalization, international migration of labour and inflows of foreign capital might produce unfavourable effects on the wage inequality in the South given the specific structural characteristics of the less developed countries, such as features of labour markets, structures of production, nature of capital mobility etc.…”
mentioning
confidence: 99%
“…According to them, inflows of foreign capital induced greater production of skilled-intensive commodities in Mexico, thereby leading to a relative decrease in the demand for unskilled labour. Marjit, Beladi and Chakrabarti (2004) have analyzed how diverse trade pattern and market fragmentation in world trade can adversely affect the skilled-unskilled wage inequality in the developing countries. They have also studied the consequences of an improvement of terms of trade and inflows of foreign capital on wage inequality with or without trade fragmentation.…”
mentioning
confidence: 99%
“…Theoretically, the falling wage gap in the post reform period has been explained in the work of Feenstra and Hanson (1996), Marjit et al (2000), Marjit et al (2004), Marjit and Acharyya (2003), Chaudhuri and Yabuuchi (2007), and Yabuuchi and Chaudhuri (2007). Feenstra and Hanson (1996) have shown that an-inflow of foreign capital has led to the increased production of skilled intensive commodities in Mexico, thereby causing a falling demand for unskilled labor.…”
Section: Introductionmentioning
confidence: 99%
“…The scanty theoretical literature explaining the deteriorating wage inequality in the Southern countries includes works of Feenstra and Hanson (1996), Marjit, Beladi and Chakrabarti (2004), Marjit and Kar (2005), Chaudhuri and Yabuuchi (2006), and Yabuuchi and Chaudhuri (2006). They have shown how trade liberalization, inflows of foreign capital and international mobility of labour both skilled and unskilled might produce unfavorable effects on the wage inequality in the South given the specific structural characteristics of the less developed countries, such as features of labour markets, structures of production, nature of capital mobility among others.…”
Section: Introductionmentioning
confidence: 99%